The cystic fibrosis transmembrane conductance regulator (CFTR) and its stability - Meng, Xin (Cell Mol Life Sci, 2016)
The cystic fibrosis transmembrane conductance regulator (CFTR) is responsible for the disease cystic fibrosis (CF). It is a membrane protein belonging to the ABC transporter family functioning as a chloride/anion channel in epithelial cells around the body. There are over 1500 mutations that have been characterised as CF-causing; the most common of these, accounting for ~70 % of CF cases, is the deletion of a phenylalanine at position 508. This leads to instability of the nascent protein and the modified structure is recognised and then degraded by the ER quality control mechanism. However, even pharmacologically ‘rescued’ F508del CFTR displays instability at the cell’s surface, losing its channel function rapidly and it is rapidly removed from the plasma membrane for lysosomal degradation. This review will, therefore, explore the link between stability and structure/function relationships of membrane proteins and CFTR in particular and how approaches to study CFTR structure depend on its stability. We will also review the application of a fluorescence labelling method for the assessment of the thermostability and the tertiary structure of CFTR.